Exploration of Pyrazolo[1, 5‐a]pyrimidines as Membrane‐Bound Pyrophosphatase Inhibitors. (12th October 2021) - Johansson, Niklas G.; Dreano, Loïc; Vidilaseris, Keni; Khattab, Ayman; Liu, Jianing; Lasbleiz, Arthur; Ribeiro, Orquidea; Kiriazis, Alexandros; Boije af Gennäs, Gustav; Meri, Seppo; Goldman, Adrian; Yli‐Kauhaluoma, Jari; et al.
Abstract: Inhibition of membrane‐bound pyrophosphatase (mPPase) with small molecules offer a new approach in the fight against pathogenic protozoan parasites. mPPases are absent in humans, but essential for many protists as they couple pyrophosphate hydrolysis to the active transport of protons or sodium ions across acidocalcisomal membranes. So far, only few nonphosphorus inhibitors have been reported. Here, we explore the chemical space around previous hits using a combination of screening and synthetic medicinal chemistry, identifying compounds with low micromolar inhibitory activities in the Thermotoga maritima mPPase test system. We furthermore provide early structure‐activity relationships around a new scaffold having a pyrazolo[1, 5‐ a ]pyrimidine core. The most promising pyrazolo[1, 5‐ a ]pyrimidine congener was further investigated and found to inhibit Plasmodium falciparum mPPase in membranes as well as the growth of P. falciparum in an ex vivo survival assay. Abstract : Chemical space exploration : Novel low micromolar membrane‐bound pyrophosphatase (mPPase) inhibitors based on an exploratory screening against Thermotoga maritima mPPase followed by early SARs around a pyrazolo[1, 5‐ a ]pyrimidine scaffold. Compound 17 a retained activity against Plasmodium falciparum mPPase in membranes, and inhibited parasite growth ex vivo .